(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. The prevalence of corneal astigmatism in patients with cataract has not been well documented in both rural and urban areas of Indian population. Purpose. The aim of this study was to assess prevalence of corneal astigmatism before cataract surgery in adult age group population of rural Andhra Pradesh. Materials and methods. A Prospective, cross-sectional, and observational study was carried out from March 2019 to December 2019 in patients presenting for cataract surgery. Axial length, and intraocular lens power were measured, Keratometric values were measured with an auto refractokeratometer, and astigmatism was calculated. Data was analysed using SPSS software. Results. This study included 1000 eyes of 1000 patients with a mean age of 61.81 ± 8.94 years. The mean astigmatism was 0.80 ± 0.72 D and the mean keratometry was 44.12D ± 1.71 D. A total of less than 1D astigmatism is seen in 67.5% eyes, 23.3% eyes had astigmatism between 1.00 and 1.99 D, 4.6% eyes had 2-2.99D, and ≥3D in 0.8% eyes and no astigmatism in 3.8% eyes. Against the rule astigmatism was seen in 49.8% cases, with the rule astigmatism is found in 31.8% of eyes and oblique astigmatism in 14.9% of eyes. With the increasing age, the WTR percentage decreased while the ATR percentage increased. Conclusion. Our study showed that significant numbers of patients have preoperative corneal astigmatism, affecting the quality of vision after cataract surgery. Majority of patients have corneal astigmatism < 1.00D, which can be corrected by low-cost procedures like steep axis phaco, limbal relaxing incisions, and opposite clear corneal incisions, especially in developing countries like India, and less percentage of candidates require expensive toric IOLs.